Implementasi Saham Syariah dalam Investasi Sukuk dan Dampaknya terhadap pertumbuhan ekonomi - Nugraha, Adhi; Jaya, Hendra; Judi Ichwan (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2021)
The purpose of this study is to study and determine the effect of Islamic stocks, Islamic bonds (Sukuk) and Islamic mutual funds on economic growth in Indonesia for the 2019-2021 period. In 2020, the coronavirus, which is the forerunner of the Covid-19 pandemic, began to enter Indonesian territory, as a result of the pandemic the economic sector in Indonesia declined dramatically. Islamic stocks, Islamic mutual funds and sukuk are of course also affected by the impact of the pandemic, therefore the authors are interested in examining the effect of Islamic stocks, Islamic bonds (Sukuk) and Islamic mutual funds on economic growth in Indonesia for the 2019-2021 period. This study takes a population from data that has been obtained from the publications of the Financial Services Authority (OJK) and the Central Statistics Agency (BPS). The approach used in this research is a quantitative approach with multiple linear regression analysis. The type of data used in this study is secondary data, namely time series data that has been published in the 2019-2021 period.